An ascent guidance algorithm for the energy management of solid rockets. (March 2020) - Cheng, Xiaoming; Zhang, Ran; Zeng, Xijuan; Li, Huifeng
Abstract: Efficient energy management for the solid rocket is very important to exhaust excess energy and to meet the various terminal constraints. Based on the online planning of the velocity capability curve, a Double-arcs Energy Management (DAEM) guidance algorithm is proposed in this paper. In the DAEM, the velocity capability curve is designed with two tangential arcs. By using the elegant geometric characteristic of the arcs, the closed-loop guidance problem is transformed as a problem of solving a system of nonlinear equations about the parameters (radius and center position) of the two arcs, and the nonlinear equations can be solved in real time. The main advantages of this algorithm are that the height increment constraint, which is difficult to be satisfied in traditional energy management methods, can be satisfied theoretically, and the convergence of the solution of the DAEM is quadratic. The effectiveness and advantages of the proposed DAEM algorithm are demonstrated by simulations and comparisons with other energy management algorithms. Highlights: A Double-arcs Energy Management (DAEM) algorithm is presented by using the geometric characteristic of the double-arcs velocity capability curve. The solution of the DAEM algorithm is analyzed to be at least quadratic convergence, which means that the guidance command can be obtained in real time. The feasibility and effectiveness of the proposed DAEM algorithm are illustrated by carefully designed tests and the comparisons with other traditional energy management algorithms.